2011
DOI: 10.4304/jltr.2.1.188-195
|View full text |Cite
|
Sign up to set email alerts
|

Field-dependence/independence as a Factor Affecting Performance on Listening Comprehension Sub-skills: the Case of Iranian EFL Learners

Abstract: Abstract-The purpose of this study was to determine if field-dependence/ independence (FD\I) cognitive style was related to the performance of Iranian EFL learners on listening comprehension sub-skills. More specifically, the study attempted to focus on three listening comprehension sub-skills, namely listening for main idea, listening for specifics, and making inference. The choice of these sub-skills was based on Weir' (1993) taxonomy. The study also tried to investigate the effect of FD\I on listening compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 18 publications
0
10
1
2
Order By: Relevance
“…The finding of this study negated the finding of another study with 80 participants, Kheirzadeh and Kassaian (2011) concluded that field-dependence/independence did not affect listening comprehension in general and listening comprehension sub-skills in special. The reason for this is not immediately apparent but was perhaps due to difference in the population, geographical location and the subject used in the study.…”
Section: Discussioncontrasting
confidence: 92%
“…The finding of this study negated the finding of another study with 80 participants, Kheirzadeh and Kassaian (2011) concluded that field-dependence/independence did not affect listening comprehension in general and listening comprehension sub-skills in special. The reason for this is not immediately apparent but was perhaps due to difference in the population, geographical location and the subject used in the study.…”
Section: Discussioncontrasting
confidence: 92%
“…However, in some other areas of literature, the result of current study is in contrast and disagreement with some studies done. For instance, Kheirzadeh and Kassaian (2011) found that there was no difference in the performance of FD and FI students on general listening comprehension and in another similar research Altun-Cakan (2006) showed that there was no significant relationship between cognitive style and academic achievement. The findings of Li-fang Zhang (2003) showed that the Field Dependence/Independence and the thinking style constructs were unrelated.…”
Section: Discussionmentioning
confidence: 99%
“…Messick (1984) defined cognitive styles as information processing habits representing the learner's typical mode of perceiving, thinking, problem solving and remembering. Ngeow (1999, as cited in Kheirzadeh & Kassaian, 2011), summarized the main benefits of cognitive styles as follow:…”
Section: Cognitive Stylementioning
confidence: 99%
See 1 more Smart Citation
“…Pada saat menuliskan data yang diketahui dan yang ditanyakan, SFI cenderung menggunakan notasi matematika dan menggunakan bahasanya sendiri. Hal ini sesuai dengan pernyataan Kheirzaden & Kassaian (2011) yaitu ketika bidangnya tidak diorganisir secara jelas, individu FI relatif cenderung menerapkan struktur mereka sendiri, sedangkan individu FD menerima seperti apa adanya.…”
Section: Pembahasan Pemecahan Masalah Generalisasi Pola Subjek Field unclassified